Evaluation of China’s fertility policy based on PMC modeling - Jie Chen; Yan Gao; Xi Wang; Xi Wang (Frontiers in Public Health)
BackgroundThe fertility level has declined to below replacement level in many countries. Hence, evaluating the fertility policies is crucial for policy intervention to achieve sustainable development. However, research on assessing fertility policies remains limited.Objective/methodologyThis study introduces a Policy Maturity and Consistency (PMC) index model based on text mining techniques to analyze 22 fertility policy documents. The analysis model aims to identify policy deficiencies and provide actionable insights for improving future policy frameworks.ResultsOur study shows that, despite a comprehensive design and high consistency, significant gaps remain in areas such as policy objectives and thematic focus. Specific recommendations are proposed to enhance policy effectiveness, including fostering multi-stakeholder collaboration, integrating economic and policy-based support mechanisms, and promoting a shift in reproductive culture.